1966
DOI: 10.1104/pp.41.6.913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Intensity on Photosynthetic Carboxylative Phase Enzymes and Chlorophyll Synthesis in Greening Leaves of Hordeum vulgare L

Abstract: Summary. The effects of various light intensities on in vivo increases in activities of phosphoriboisomerase, phosphoribulokinase and ribulose-1,5-diP carboxylase and on synthesis of chlorophyll were studied in greening leaves of Hordeutn vullgare L.Each enzyme was already present in dark-grown plants, but further increases in activities required both a light treatiment of the intact plant and a favorable temperature. The amount of enzymatic activity and chlorophyll developed was governed bv light intensity.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Although light-initiated increases in enzymatic activities did not occur without chlorophyll accumulation, the relationship may still be indirect between activities of the carboxylative phase enzymes and accumulation of chlorophyll. Huffaker et al (7) showed that the linear correlation of phosphoribulokinase activity with chlorophyll content was lost at low intensities of illumination. Benedict and Kohel (2) recently reported that the increase in activity of ribulose-1,5-diP carboxylase is not correlated with chlorophyll accumulation in virescent cotton leaves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although light-initiated increases in enzymatic activities did not occur without chlorophyll accumulation, the relationship may still be indirect between activities of the carboxylative phase enzymes and accumulation of chlorophyll. Huffaker et al (7) showed that the linear correlation of phosphoribulokinase activity with chlorophyll content was lost at low intensities of illumination. Benedict and Kohel (2) recently reported that the increase in activity of ribulose-1,5-diP carboxylase is not correlated with chlorophyll accumulation in virescent cotton leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Distribution of area of 50 leaf sections, phosphoriboisomerase activity, phosphoribulokinase activity, ribulose-l , 5-diP carboxylase activity, soluble protein, and total chlorophyll in different leaf sections after various periods of illumination. All seedlings were grown in darkness for 7 days before illumination at 10,760 lux. Standard errors of the difference between means of illumination periods within a section, and between section means within an illumination period, respectively, were 1.9, 2.6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In barley leaves, several of these processes proceed very rapidly during the first 24 hrs of light and reach a steady state sometime after about 36 to 48 hr of light (6). Hellebust and Bidwell (5) observed that turnover of soluble protein in wheat leaves was fastest when the leaves were either growing or biochemically differentiating.…”
Section: Methodsmentioning
confidence: 99%
“…After growth or biochemical differentiation was completed, the turnover was very slow. Growth was not a confounding factor in our work, since the experiments were begun only after the first leaf had completed its growth (6 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%